Opera Van Java di Mata Penonton Etnis Luar Jawa (Kajian Etnografi Komunikasi Khalayak Penonton dari Etnis Luar Jawa terhadap Tayangan Opera Van Java) - Annisa Risecha Junep (Jurnal Komunikasi, 2012)
Opera Van Java (OVJ) is a comedy program in an Indonesian television program, Trans 7. The idea of the show is a modernized human puppet show. The actors in the OVJ are given instruction to improvise themselves without memorizing the script, led by a Puppet Master (Dalang). This article will discuss the reception of the students of non Javanese ethnic towards OVJ. This is involved in the subject environment in order to know how they respond and perceive toward OVJ. The result is that most of the audiences from non Javanese ethnic like the OVJ show because of the unique stories and the funny actors that are presenting the show. Besides, the concept of the show that brings the Javanese theme allows the non Javanese ethnic audiences understand about Javanese culture.